Confirmation of Transit Time-Limited Field Emission in Advanced Carbon Materials with a Fast Pattern Recognition Algorithm - Posos, Taha Y.; Chubenko, Oksana; Baryshev, Sergey V. (ACS applied electronic materials, 2021)
Not provided.